Extensive migration of young neurons into the infant human frontal lobe - Mercedes F. Paredes; D. J. James; Sara Gil‐Perotín; Hosung Kim; Jennifer Cotter; Carissa Ng; Kadellyn Sandoval; David H. Rowitch; Duan Xu; Patrick S. McQuillen; José Manuel García‐Verdugo; Eric J. Huang; et al. (2016)
Building the human brain As the brain develops, neurons migrate from zones of proliferation to their final locations, where they begin to build circuits. Paredes et al. have discovered that shortly after birth, a group of neurons that proliferates near the ventricles migrates in chains alongside circulatory vessels into the frontal lobes (see the Perspective by McKenzie and Fishell). Young neurons that migrate postnatally into the anterior cingulate cortex then develop features of inhibitory interneurons. The number of migratory cells decreases over the first 7 months of life, and by 2 years of age, migratory cells are not evident. Any damage during migration, such as hypoxia, may affect the child's subsequent physical and behavioral development. Science , this issue p. 81 ; see also p. 38